FIXED-POINT THEOREMS USING INTERPOLATIVE BOYD-WONG-TYPE CONTRACTIONS AND INTERPOLATIVE MATKOWSKI-TYPE CONTRACTIONS ON PARTIAL 𝑏-METRIC SPACES - A. Gupta; R. Mansotra (Проблемы анализа)
This article introduces interpolative contractions of both Boyd-Wong and Matkowski types in the framework of partial 𝑏-metric spaces. We derive fixed-point theorems for these two contractions and incorporate examples to emphasize the practical relevance of our findings.